Clinical Risk Factors for Gastroduodenal Ulcer in Romanian Low-Dose Aspirin Consumers - Anca Negovan; Mihaela Iancu; Valeriu Moldovan; Septimiu Voidazan; Simona Bataga; Monica Pantea; Kinga Sarkany; Cristina Tatar; Simona Mocan; Claudia Banescu (Gastroenterology Research and Practice)
Background. Aspirin use for cardiovascular or cancer prevention is limited due to its gastrointestinal side effects. Objective. Our prospective, observational case-control study aims to identify the predictive factors for ulcers in low-dose aspirin consumers (75–325 mg/day). Methods. The study included patients who underwent an upper digestive endoscopy and took low-dose aspirin treatment. Results. We recruited 51 patients with ulcer (ulcer group) and 108 patients with no mucosal lesions (control group). In univariate analysis, factors significantly associated with ulcers were male gender (p=0.001), anticoagulants (p=0.029), nonsteroidal anti-inflammatory drugs (p=0.013), heart failure (p=0.007), liver (p=0.011) or cerebrovascular disease (p=0.004), diabetes mellitus (p=0.043), ulcer history (p=0.044), and alcohol consumption (p=0.018), but not Helicobacter pylori infection (p=0.2). According to our multivariate regression analysis results, history of peptic ulcer (OR 3.07, 95% CI 1.06–8.86), cotreatment with NSAIDs (OR 8, 95% CI 2.09–30.58) or anticoagulants (OR 4.85, 95% CI 1.33–17.68), male gender (OR 5.2, 95% CI 1.77–15.34), and stroke (OR 7.27, 95% CI 1.40–37.74) remained predictors for ulcer on endoscopy. Conclusions. Concomitant use of NSAIDs or anticoagulants, comorbidities (cerebrovascular disease), and male gender are the most important independent risk factors for ulcer on endoscopy in low-dose aspirin consumers, in a population with a high prevalence of H. pylori infection.